Сложные слова в оригинале и переводе (на материале романа А. Пушкина "Евгений Онегин" и его перевода на украинский язык) - Приймачок, Оксана Іванівна; Pryimachok, Oksana I. (Дніпропетровський університет імені Альфреда Нобеля, 2013)
В статье описаны лексемы со сложной словообразовательной структурой (композиты), употреблённые А.С.Пушкиным в его романе в стихах «Евгений Онегин», с точки зрения их перевода на украинский язык, осуществлённого М.Ф.Рыльским. Проанализированы основные способы и приёмы перевода данных слов, выделены типичные и оригинальные техники перевода. На многочисленных примерах продемонстрировано настоящее мастерство Рыльского-переводчика. The article describes the composite words in the A.Pushkin’s novel “Eugene Onegin” and in Ukrainian translation which is made by M.Rylskiy; gives a characterization of their semantic and derivational structure. The basic techniques and methods for translate those words into Ukrainian language are classified. Many examples show the mastery of Rylskyj-translator, especially on the lexical level.

The article describes the composite words in the A.Pushkin’s novel “Eugene Onegin” and in Ukrainian translation which is made by M.Rylskiy; gives a characterization of their semantic and derivational structure. The basic techniques and methods for translate those words into Ukrainian language are classified. Many examples show the mastery of Rylskyj-translator, especially on the lexical level.
Keywords: перевод; славянские языки; сложные слова (композиты); translate; Slavonic languages; composite words; translation